God and design : the teleological argument and modern science - Manson, Neil A., 1967- (Routledge, 2003)
Recent discoveries in physics, cosmology, and biochemistry have captured the public imagination and made the Design Argument - the theory that God created the world according to a specific plan - the object of renewed scientific and philosophical interest. This accessible but serious introduction to the design problem brings together new perspectives from prominent scientists and philosophers including Paul Davies, Richard Swinburne, Sir Martin Rees, Michael Behe, Elliot Sober and Peter van Inwagen. It probes the relationship between modern science and religious belief, considering their points of conflict and their many points of similarity. Is the real God of creationism the 'master clockmaker' who sets the world's mechanism on a perfectly enduring course, or a miraculous presence who continually intervenes in and alters the world we know? Are science and faith, or evolution and creation, really in conflict at all? Expanding the parameters of a lively and urgent debate, God and Design considers how perennial questions of origin continue to fascinate and disturb us.